Application of continuous nursing in the postoperative management of patients following coronary artery stenting (延续性护理在冠状动脉支架植入术后患者康复管理中的应用现状) - WANG Zhaojia (王兆嘉) (中西医结合护理)
Stent implantation is an effective treatment for coronary heart disease, effectively keeps the artery open, improves blood flow to the heart and relieves symptoms like chest pain. Postoperative patients require lifelong secondary preventive medications to control various risk factors and reduce adverse cardiovascular events. Continuous nursing plays an important role in improvement of patient outcome after surgery. This paper briefly introduced the coronary artery stenting and reviewed relevant studies on continuous nursing service in postoperative management of patients following coronary artery stenting, and provided reference for postoperative recovery. (冠状动脉支架植入术是治疗冠心病常用术式, 能有效帮助病变的血管恢复畅通, 改善患者病情。冠状动脉支架植入术后患者需终身服用二级预防药物, 全面控制各种危险因素, 减少心血管不良事件。延续性护理对改善冠状动脉支架植入术后患者预后有着重要作用。本研究就冠状动脉支架植入术的概念以及延续性护理在冠状动脉支架植入术后患者康复管理中常见的服务内容进行综述, 旨在为提高PCI患者术后康复效果提供参考。)